Insilico Prediction of Biological Activity of Secondary Metabolites of Amphora sp.: for Development of Natural Medicines - Ach. Khumaidi; Abdul Wafi; Abdul Muqsith (Airlangga University, 2021)
Diatom Amphora sp. is a type of aquaculture product that has various types of metabolites with very good potential to be used as basic ingredients for drugs or other health products. Insilico analysis of extracts of Amphora sp. was carried out to predict biological activity that can be used as a basis for developing the use of aquaculture products. The research was conducted by extracting Amphora sp. using ethanol solvent with sonication method, the extraction results were analyzed by LC-HRMS, and the metabolite readings were then analyzed for drug potential and biological activity online using swissADME, Protox II, and Way2Drug applications. The results of the LC-HRMS analysis showed that the extracted Amphora sp. showed the highest abundance of valine compounds with 17.6% as well as other compounds L-Norleucin, stearamide, palmitoleic acid, isotretinoin, and arachidonic acid. The results of the ADME/T analysis showed that the six compounds of Amphora sp. extract had quite good potential according to the Lipinski rule of five. Biological activity also shows potential as an anti-inflammatory, antifungal, antibacterial, antiviral, and antineoplastic agent with Pa values ranging from 0.260 to 0.873. These results indicate that the production development of Amphora sp. and its use is very wide, including in the health sector. Keyword: ADME/T, PASSonline, Amphora sp., sonication, aquaculture